Fatigue 7 years post‐stroke: Predictors and correlated features. (5th July 2022) - Pedersen, Annie; Almkvist, Emelie; Holmegaard, Lukas; Lagging, Cecilia; Redfors, Petra; Blomstrand, Christian; Jood, Katarina; Samuelsson, Hans; Jern, Christina
Abstract : Background: Post‐stroke fatigue (PSF) is common with great impact on quality of life. We explored predictive and cross‐sectionally correlated features in the long term after ischemic stroke. Methods: This study comprises 430 participants of the prospective Sahlgrenska Academy Study on Ischemic Stroke (SAHLSIS), aged 18–69 years at index stroke. Information on acute stroke severity and cardiovascular risk factors was collected at index stroke. After 7 years, PSF was assessed by the Daily Fatigue Impact Scale (D‐FIS). Cognitive, neurological, and functional outcomes, and symptoms of depression and anxiety, pain, insomnia, and physical activity were also assessed. Associations between baseline variables and PSF were analyzed by ordinal regression. Correlations between PSF and cross‐sectionally assessed variables, and between PSF and baseline variables, were analyzed with Spearman's or point‐biserial correlation for the whole sample and in sex‐stratified analyses. Results: At 7 years post‐stroke, 80% of the participants reported some impact of fatigue. Female sex and stroke severity were independently associated with PSF, whereas no associations were detected with baseline cardiovascular risk factors. In cross‐sectional analyses at 7 years, we found correlations between PSF and poor functional, neurological, and cognitive outcomes, as well as depressive symptoms, anxiety, insomnia, pain, and low physical activity ( p  < .001 throughout). The correlation with insomnia was stronger in women than in men (two‐way ANOVA interaction test, p  = .03). Conclusions: Our findings confirm that PSF is common in the long term after ischemic stroke and show a complex interplay with sex and several other outcomes. Future studies should address causal relationships and interventions towards fatigue and coexisting features.